2018
DOI: 10.1111/ijag.12352
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of stained‐glass windows materials by infrared thermography

Abstract: This paper reports the analyses of infrared thermography images of two stained‐glass windows with the objective of the in situ characterization of this type of artworks. The analyses were carried out by active thermography. The observations revealed that glasses absorbed the long‐wave IR radiation emitted by the halogen lamps and their apparent surface temperature progressively increased. After switching the spotlight off, they experienced a progressive decrease in temperature. Silver stained glasses presented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 58 publications
(96 reference statements)
2
15
0
Order By: Relevance
“…The temperature variation between both materials was less than 2 °C in all the cases, which indicates a good thermal compatibility. Similar results were observed in previous studies [16,19].…”
Section: Thermographic Characterisationsupporting
confidence: 93%
See 1 more Smart Citation
“…The temperature variation between both materials was less than 2 °C in all the cases, which indicates a good thermal compatibility. Similar results were observed in previous studies [16,19].…”
Section: Thermographic Characterisationsupporting
confidence: 93%
“…The IR-thermographic analyses were made in reflection mode on grisailles with different thickness (thicker, medium and thinner) painted on common window glass to understand their thermal behaviour [16][17][18][19]. The samples are showed in Figure 6.…”
Section: Thermographic Characterisationmentioning
confidence: 99%
“…This enhanced absorbance will produce an increase in the overall temperature of the enamel and also a thermal mismatch between particles, enamel glass and base glass. The differences in the thermal expansion coefficients between particles/enamel glass and between the enamel and the base glass are expected to give rise to the formation of cracks Finally, supporting our data, recent studies using Infrared Thermography have shown that dark enamels and grisailles show an increase of the temperature 40% higher than those of the transparent glass [38,39] and about 20% higher than other colour enamels.…”
Section: Fig 5bsupporting
confidence: 90%
“…These latter materials normally are rough dark paints with iron oxides in their composition. This favors an intense absorption of the thermal radiation, increasing their temperature [36].…”
Section: Impact Of Surface Paintsmentioning
confidence: 99%
“…This technique has been applied to evaluate the thermal efficiency of different windows systems [21,22], as well as, to evaluate glasses with different industrial purposes [23][24][25][26], to research fire endurance of tempered glass [27], to study the mechanical defects and the elastic deformations on glass sheets [28][29][30][31][32], and to analyze the efficiency of solar cells [33,34]. The application of IRthermography on historical glasses is scarce [20,32,33]; nevertheless, these studies proved to be a useful tool to evaluate the conservation of historical stained-glass windows [35,36].…”
Section: Introductionmentioning
confidence: 99%